2002
DOI: 10.2136/sssaj2002.1311
|View full text |Cite
|
Sign up to set email alerts
|

Organic Amendment and Rotation Crop Effects on the Recovery of Soil Organic Matter and Aggregation in Potato Cropping Systems

Abstract: der et al., 1994). Water soluble carbohydrates directly stabilize aggregates (Angers and Mehuys, 1989) and Soil structural degradation is common in intensively cultivated have been strongly correlated (r ϭ 0.74) with aggregaecosystems due to the depletion of soil organic matter (SOM). We tion (Haynes and Swift, 1990). investigated the mechanisms by which different frequencies of organic amendment application and rotation crops restore C, N, and aggrega-Green manure crops increase soil C inputs, but their tion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 32 publications
5
87
0
4
Order By: Relevance
“…Nutrient cycling and accumulations in potato production systems are also important to understand, as applications of fertilizers often need to be adjusted to compliment the nutrient supply from the manure source. Grandy et al (2002) found that fields receiving 16 t ha −1 cattle manure 6 years prior to potato production did not affect soil bulk density, but soil carbon content increased by 46% and medium and large soil aggregate content increased in comparison to the field that had not received manure. Curless et al (2005) found that potatoes consumed excess phosphorus (P) from fertilizer sources, but not from manure sources.…”
Section: Introductionmentioning
confidence: 87%
“…Nutrient cycling and accumulations in potato production systems are also important to understand, as applications of fertilizers often need to be adjusted to compliment the nutrient supply from the manure source. Grandy et al (2002) found that fields receiving 16 t ha −1 cattle manure 6 years prior to potato production did not affect soil bulk density, but soil carbon content increased by 46% and medium and large soil aggregate content increased in comparison to the field that had not received manure. Curless et al (2005) found that potatoes consumed excess phosphorus (P) from fertilizer sources, but not from manure sources.…”
Section: Introductionmentioning
confidence: 87%
“…Comparisons for MWD, compared between the present and earlier study, showed that the MWD remained B1.0 for the 2-yr conventional tillage, but increased from 1.3 to 1.6 for the 3-yr conservation tillage. Grandy et al (2002) and Carter et al (2003) showed that organic amendments and rotation crop effects can improve soil aggregation even in short-term potato rotations. This was expressed by increases in the proportion of large ( 1 and 2 mm) aggregates in the 3-yr rotation (Fig.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Length of crop rotation and frequency of potato cropping, use of leguminous companion-crops, and type of soil management system have an important bearing on soil biological parameters, such as soil organic matter fractions (Grandy et al 2002;Carter et al 2003), soilborne diseases (Leach et al 1993;Peters et al 2004Peters et al , 2005, root lesion nematode populations (Kimpinski et al 2000;, and microarthropod communities (Fox et al 1999;Carter and Noronha 2007). In many cases, the above changes in soil biological properties take a significant time period (e.g.,5 yr) before they become evident, and thus require relatively long-term studies for their evaluation .…”
mentioning
confidence: 99%
See 2 more Smart Citations